Turing Pattern‐Inspired Highly Transparent Wood for Multifunctional Smart Glass with Superior Thermal Management and UV‐Blocking Ability. (22nd May 2022) - Zhou, Jiazuo; Liu, Yifan; Yang, Zhaolin; Wang, Xin; Li, Yudong; Liu, Feng; Jiang, Zishuai; Sun, Xiaohan; Li, Xiaowang; Zhao, Yusen; Wang, Chengyu; Ho, Shih‐Hsin; et al.
Abstract: Transparent wood for smart glass can decrease indoor energy consumption, while simultaneously offering a comfortable indoor temperature and facilitating effective light harvesting. However, high transparency and ultraviolet (UV)‐blocking ability are mutually exclusive in wood‐based materials due to the presence of lignin. Herein, a Turing pattern‐inspired highly transparent wood (TP‐TW) is fabricated via infiltrating the thermal management materials doped‐epoxy (TMM‐epoxy) into the delignified wood with a Turing pattern. Afterward, the Turing pattern possesses outstanding optical properties (high visible transmittance of ≈ 76% and low UV transmittance of ≈ 15%). Moreover, TP‐TW can reduce adverse effects caused by indoor temperature fluctuation and outdoor sunlight, demonstrating high latent heat (25.30 J g −1 ) and low near‐infrared transmittance. Compared with glass, TP‐TW exhibits a low thermal conductivity of 0.21 W m −1 K −1 and excellent shock‐resistant characteristics. Taken together, these results indicate that TP‐TW is an attractive material for smart glass applications. Abstract : The periodic changes in the activity of cambium cells result in the formation of an alternate structure of earlywood and latewood (LW). A small proportion of the lignin in the LW is preserved, which leads to the fabrication of Turing pattern‐inspired highly transparent wood (TP‐TW) with excellent UV‐absorbing ability. Addtionally, TP‐TW demonstrates high latent heat and low near‐infrared transmittance.